THE EFFECT OF GIVING TYPES OF FEED AND DIFFERENT DOSES ON POPULATION GROWTH Daphnia magna - Rahmadani, Rizka; Nuraini, Nuraini; Sukendi, Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThis research was conducted on 1 September-1 October 2018 at the Laboratory of Fish Hatchery and Breeding, Faculty of Fisheries and Marine Sciences, Riau University. The purpose of this study is to determine the effect of feed types and different doses on the population growth of Daphnia magna so as to produce the highest population growth. The method used in this study was a 2 factor Complete Random Design (CRD) method and 6 treatment levels were carried out 3 replications to obtain 18 experimental units. The treatment in this study was the provision of yeast feed, tofu pulp and sago pulp with a dose of 1.0 g/l and 1.5 g/l. The results showed that administration of different types of feed and dosage had a significant effect (P <0.05) on the population growth of Daphnia magna. The highest population growth of Daphnia magna was produced by treatment with 1.5 g/l doses of Yeast with an average population of 468.33 ind/l and the lowest population was found in sago pulp treatment with an average population growth of 221.67 ind/l. The water quality parameter values obtained during the study showed a good range for the growth of Daphnia magna, namely temperatures ranging from 24.0-30ºC and pH 6-7,9. Keywords :Daphnia magna, different feeds, different doses, population growth